2014
DOI: 10.1111/ejn.12798
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in the lateral septum increases sucrose intake and decreases anorectic effects of stress

Abstract: Sucrose-overeating rats with decreased anorectic response to stress showed lower stress-induced activation of c-fos expression in the lateral septum (LS). The present study tested a hypothesis that neuronal inhibition in the LS is important for the development and maintenance of the sucrose-overeating phenotype. Sucrose overeating was developed with weekly episodes of food restriction (21 h per day, 4 days per week) followed by 1-h access to sucrose. The anorectic effects of stress on 1-h sucrose intake were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…This activation is likely associated with the increased interaction with food (as reflected in the increased number of bouts in activity-based anorexia rats compared to the ad libitum group) as well as the stimulated food intake during the 1.5-h feeding period. In line with this assumption, key areas of food intake regulation were activated as well, namely the lateral septal nucleus (Mitra et al, 2015), lateral hypothalamic area (Bernardis and Bellinger, 1993), the dorsomedial hypothalamic nucleus and the medial part of the Arc, both expressing the potent orexigenic transmitter neuropeptide Y (Wang et al, 2002; Bi et al, 2012) and lastly also the nucleus of the solitary tract (Stengel and Taché, 2011). Further corroborating the involvement of these nuclei in the orexigenic drive under conditions of activity-based anorexia, a previous study reported a robust upregulation of orexigenic agouti-related peptide and neuropeptide Y, whereas the anorexigenic transmitters pro-opiomelanocortin (POMC) and cocaine- and amphetamine-regulated transcript (CART) were reduced in the Arc of activity-based anorexia rats compared to sedentary food-restricted controls (de Rijke et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…This activation is likely associated with the increased interaction with food (as reflected in the increased number of bouts in activity-based anorexia rats compared to the ad libitum group) as well as the stimulated food intake during the 1.5-h feeding period. In line with this assumption, key areas of food intake regulation were activated as well, namely the lateral septal nucleus (Mitra et al, 2015), lateral hypothalamic area (Bernardis and Bellinger, 1993), the dorsomedial hypothalamic nucleus and the medial part of the Arc, both expressing the potent orexigenic transmitter neuropeptide Y (Wang et al, 2002; Bi et al, 2012) and lastly also the nucleus of the solitary tract (Stengel and Taché, 2011). Further corroborating the involvement of these nuclei in the orexigenic drive under conditions of activity-based anorexia, a previous study reported a robust upregulation of orexigenic agouti-related peptide and neuropeptide Y, whereas the anorexigenic transmitters pro-opiomelanocortin (POMC) and cocaine- and amphetamine-regulated transcript (CART) were reduced in the Arc of activity-based anorexia rats compared to sedentary food-restricted controls (de Rijke et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…Nucleus accumbens core and shell neurons, other key targets of VTA dopamine signaling, receive substantial innervation from the vSub (8688). The lateral septum, recently associated with the control of gastric motility (89, 90) and sucrose hyperphagia (91), is another potential feeding-relevant efferent pathway arising from vSub (92, 93) and dorsal CA3 neurons (94). We hypothesize that these monosynaptic outputs from the hippocampus to hypothalamic, striatal, prefrontal cortical, and septal outputs are critical downstream targets for hippocampal neural processing of interoceptive feeding-relevant information.…”
Section: Neuroanatomical Connectivitymentioning
confidence: 99%
“…Similar to NAc D1R neurons, synaptic and neural alterations in the septal nucleus are also implicated in emotion-based feeding disorders [3638]. In particular, inhibition of lateral septum neurons blocked stress-induced reductions in food intake [38], although it remains unclear if septal GABAergic projections to LH GABAergic neurons are involved in the role of lateral septum in stress-induced alterations in feeding, or other components of emotional behavior. However, given that septum both modulates feeding [35, 3941] and affective behaviors [31], septal inputs to LH appear poised to govern emotional components of feeding behavior.…”
Section: Lh Gabaergic Neurons Receive Inputs From Emotional Circuitrymentioning
confidence: 99%